Translation Techniques and Translation Quality of Indonesian Subtitles of Coco Movie: A Comparative of Two Subtitlers - Annisa Risma Khairani Lubis; Muhizar Muchtar; Umar Mono (Universitas Cokroaminoto Palopo, 2020)
The objectives of the research are to identify the types of translation technique, to evaluate the translation quality and to find out the effect of translation techniques on the translation quality used by Pein Akatsuki and Deni Aurora in Indonesian subtitles of Coco movie. This research applies descriptive qualitative method to assess data with documents and informants as source of data. The result shows that there are 16 types of translation techniques used by Pein Akatsuki and Deni Aurora in translating Indonesian subtitles. For both subtitlers, literal translation and borrowing create high level of accuracy, acceptability, and readability. Modulation and the other techniques are showed in high and medium levels of accurate translation, but they result in high levels of acceptability and readability. Based on the findings, the translation techniques applied by the subtitlers contribute positively to the quality of Indonesian subtitles in terms of accuracy, acceptability, and readability.